EVOLUSI PEMIKIRAN MANAJEMEN SYARIAH TINJAUAN LITERATUR DARI PERSPEKTIF HISTORIS - Abdurrohman Akbar, Firman Muhammad; Lazuardi, Afried; Haniatunnisa, Siti (Sekolah Tinggi Ilmu Fikih Syeikh Nawawi Tanara Serang, 2024)
The evolution of Islamic management practices has significantly transformed from the classical to contemporary eras, demonstrating adaptability to social, economic, and global changes while adhering to Islamic principles such as faith, charity, and musawarah. This study aims to analyze the evolution of Islamic management practices and how Islam can be integrated into modern management practices. The research methodology uses qualitative research with literature and relevant sources to analyze the development and contributions of Islamic management practices over time. The findings show that Islamic management not only has relevance in Islamic business but also contributes to conventional management through ethics, value-based leadership, transparency, and accountability. Despite challenges in implementation, such as lack of standard standards and compliance with conventional business, this evolution highlights the importance of Islamic management in addressing global dynamics and creating an organization that supports and guides the Islamic community.